Zastosowanie mikroskopii konfokalnej do diagnostyki różnicowej zapaleń rogówki - Mrukwa-Kominek, Ewa; Gierek-Ciaciura, Stanisława; Rokita-Wala, Iwona; Pierzchała, Aleksandra (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
In the course of keratitis, the early diagnosis is very important to start with the effective treatment. Clinical state and slit lamp biomicroscopic examination not always allows to establish etiologic factor. In this paper, usefulness of the confocal microscopy in vivo examination to diagnose cases of not clear etiology in corneal inflammation, was presented. Authors presented the correlation between the clinical signs and the confocal images basis in five examined patients.